Variation in WNT7A is unlikely to be a cause of familial Congenital Talipes Equinovarus - Hennekam Raoul; Sahota Sukhy; Shaw Duncan; Cardy Amanda; Inglis Julie; Liu Guoqing; Sharp Linda; Miedzybrodzka Zosia (BMC, 2008)
Abstract Background Genetic factors make an important contribution to the aetiology of congenital talipes equinovarus (CTEV), the most common developmental disorder of the lower limb. WNT7A was suggested as a candidate gene for CTEV on the basis of a genome-wide scan for linkage in a large multi-case family. WNT7A is a plausible candidate gene for CTEV as it provides a signal for pattern formation during limb development, and mutation in WNT7A has been reported in a number of limb malformation syndromes. Methods We investigated the role of WNT7A using a family-based linkage approach in our large series of European multi-case CTEV families. Three microsatellite markers were used, of which one (D3S2385) is intragenic, and the other two (D3S2403, D3S1252) are 700 kb 5' to the start and 20 kb from the 3' end of the gene, respectively. Ninety-one CTEV families, comprising 476 individuals of whom 211 were affected, were genotyped. LOD scores using recessive and incomplete-dominant inheritance models, and non-parametric linkage scores, excluded linkage. Results No significant evidence for linkage was observed using either parametric or non-parametric models. LOD scores for the parametric models remained strongly negative in the regions between the markers, and in the 0.5 cM intervals outside the marker map. No significant lod scores were obtained when the data were analysed allowing for heterogeneity. Conclusion Our evidence suggests that the WNT7A gene is unlikely to be a major contributor to the aetiology of familial CTEV.